Training workshop on the Small Reservoirs Dashboard: from data to decision - Akpoti, Komlavi; Appiah, Sarah; Zwart, Sander J. (International Water Management Institute, 2025)
The Training Workshop on the Small Reservoirs Dashboard, held in Accra and Tamale, aimed to build stakeholder capacity to use the Small Reservoirs Data Portal for aquaculture development, water management, and evidence-based planning. The portal—developed under the CGIAR Sustainable Animal and Aquatic Foods (SAAF) Program—provides integrated information on more than 2,000 reservoirs, combining satellite time-series analysis, field survey data from over 900 sites, and a geospatial aquaculture suitability assessment. Sixty participants from research institutions, government agencies, NGOs, and the private sector attended the two workshops. Presentations covered reservoir mapping using remote sensing, monitoring dry-season water availability, characterizing reservoir infrastructure and multi-use functions, and assessing aquaculture feasibility through social, economic, and biophysical indicators. In-depth demonstrations of the dashboard familiarized participants with its modules—water status monitoring, reservoir dynamics visualization, site characterization, and aquaculture suitability—followed by hands-on exercises that strengthened practical skills in data exploration and interpretation.  Participants engaged actively in discussions on reservoir performance, the diversity of reservoir types across northern Ghana, and the relevance of combining spatial data with field insights. Examples illustrated how the dashboard can support planning, extension, aquaculture development, and monitoring activities. The workshop also explored the importance of community ownership, institutional collaboration, and alignment with national water and aquaculture management frameworks.  The workshop concluded with next steps focused on expanding the portal’s content, strengthening institutional partnerships, continuing capacity-building efforts, and advancing research and business models to support responsible scaling of aquaculture in northern Ghana.